2012
DOI: 10.1021/bi300762p
|View full text |Cite
|
Sign up to set email alerts
|

PatA and PatB Form a Functional Heterodimeric ABC Multidrug Efflux Transporter Responsible for the Resistance of Streptococcus pneumoniae to Fluoroquinolones

Abstract: All bacterial multidrug ABC transporters have been shown to work as either homodimers or heterodimers. Two possibly linked genes, patA and patB from Streptococcus pneumococcus, that encode half-ABC transporters have been shown previously to be involved in fluoroquinolone resistance. We showed that the ΔpatA, ΔpatB, or ΔpatA/ΔpatB mutant strains were more sensitive to unstructurally related compounds, i.e., ethidium bromide or fluoroquinolones, than the wild-type R6 strain. Inside-out vesicles prepared from Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 50 publications
3
58
0
1
Order By: Relevance
“…Turnover rates are stimulated if the substrate binds prior to hydrolysis but there is a considerable basal consumption of ATP (Figure 1—figure supplement 2). While there is evidence of ATP turnover by impaired NBSs, consideration of the reaction mechanism as well as previous biochemical studies of ABC heterodimers support an intrinsically slower rate at the degenerate NBS (Procko et al, 2006; Zutz et al, 2011; Boncoeur et al, 2012). Therefore, ADP and Pi are released from the consensus site prior to hydrolysis at the degenerate site enabling multiple rounds of asymmetric ATP hydrolysis without the complete disengagement of the NBDs to an apo conformation.
10.7554/eLife.02740.025Figure 8.Distinct mechanisms of ABC heterodimers and homodimers.( A ) Asymmetric hydrolysis of ATP in an ABC heterodimer.
…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Turnover rates are stimulated if the substrate binds prior to hydrolysis but there is a considerable basal consumption of ATP (Figure 1—figure supplement 2). While there is evidence of ATP turnover by impaired NBSs, consideration of the reaction mechanism as well as previous biochemical studies of ABC heterodimers support an intrinsically slower rate at the degenerate NBS (Procko et al, 2006; Zutz et al, 2011; Boncoeur et al, 2012). Therefore, ADP and Pi are released from the consensus site prior to hydrolysis at the degenerate site enabling multiple rounds of asymmetric ATP hydrolysis without the complete disengagement of the NBDs to an apo conformation.
10.7554/eLife.02740.025Figure 8.Distinct mechanisms of ABC heterodimers and homodimers.( A ) Asymmetric hydrolysis of ATP in an ABC heterodimer.
…”
Section: Discussionmentioning
confidence: 94%
“…Modifications of the Walker B, signature and/or switch motifs sequences, which lead to selective catalytic impairment of one of the NBSs in a subclass of ABC exporters (Gao et al, 2000; Aleksandrov et al, 2002; Zhang et al, 2006; Procko et al, 2009; Boncoeur et al, 2012), are associated with fundamental differences in the conformational dynamics of the NBDs and in the power stroke of transport. In contrast to the ATP-induced association/dissociation cycle of NBDs in bacterial homodimers reported previously (Borbat et al, 2007; Zou et al, 2009) and further confirmed here, the NBDs of heterodimers form structurally asymmetric dimers as a consequence of ATP binding and its subsequent hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the overexpression of patA and patB genes was associated with FQ resistance in clinical isolates of S. pneumoniae and their inactivation restored susceptibility to FQ [55]. The patA (spr1887) and patB (spr1885) genes belong to the same operon and work together as heterodimers to make a functional ABC transporter [56]. Even though upregulation of patAB has been observed in many laboratory mutants and clinical isolates, the regulatory mechanisms controlling expression of these genes are still unknown and may be due to mutations in rho-independent terminator or patAB gene duplication [57,58].…”
Section: Fluoroquinolone (Fq) Resistancementioning
confidence: 99%
“…The second efflux system was revealed while characterizing 13 putative efflux systems of the ATP-binding cassette (ABC) superfamily in S. pneumoniae TIGR4 (36). The ABC transporters SP2075 (PatA) and SP2073 (PatB) were shown to act as heterodimers (37) to enable resistance to several antimicrobial agents, including ethidium bromide (EtBr), dyes, and fluoroquinolones, and the overexpression of their genes is associated with fluoroquinolone resistance in S. pneumoniae clinical isolates (30).…”
mentioning
confidence: 99%